KAJIAN STRUKTURAL PUISI MANTRA JAMPE NYEURI BEUTEUNG DI SUKU SUNDA - Noor Fadillah; Fitri Nur Amaliyah; Firda Aulia Rahmah; Indrya Mulyaningsih (ppjbsip, 2023)
Abstract: This study aims to: (1) describe the physical structure of the mantra poem